α-Klotho levels in girls with central precocious puberty: potential as a diagnostic and monitoring marker - Park, Jun-Hong; Noh, Eu-Seon; Hwang, Il Tae (Frontiers in Endocrinology, 2024)
Background: Recent studies suggest a link between the Klotho protein, sex hormones, and insulinlike growth factor-1 (IGF-1), indicating that α-Klotho levels may rise during puberty, including in central precocious puberty (CPP) cases. This study aimed to explore α-Klotho levels in girls with CPP to assess its potential as a diagnostic and monitoring tool for this condition. Methods: In total, 139 girls, comprising 82 patients diagnosed with CPP and 57 healthy prepubertal controls, were enrolled in this study. From March 2020 to May 2023, we assessed both α-Klotho levels and clinical parameters. α-Klotho concentrations were measured using an 𝛼-Klotho ELISA kit. For the girls with CPP, we additionally analyzed samples taken 6 months after GnRH agonist treatment. Results: α-Klotho levels were higher in the CPP group compared with the control (CPP group: 2529 ± 999 ng/mL; control group: 1802 ± 675 pg/mL) (P < 0.001), and its level modest decreased after 6 months of GnRH agonist treatment (2147± 789 pg/mL) (P < 0.001). The association between α-Klotho and IGF-1 SDS, follicular stimulating hormone and baseline luteinizing hormone was assessed by partial correlation after adjusting for age, BMI SDS (r= 0.416, p= <0.001; r= 0.261, p= 0.005; r= 0.278, p= 0.002), respectively. Receiver operating characteristic curve analysis identified an α-Klotho cut-off differentiating CPP from controls, with a cut-off of 1914 pg/mL distinguishing girls with CPP from controls with a sensitivity of 69.5% and specificity of 70.2%; the area under the curve was 0.723.The findings of our study are the first step towards deciphering the role of α-Klotho in puberty induction. With additional data and further research, α-Klotho could potentially be utilized as a significant diagnostic and monitoring tool for CPP.